1.given the system express y as a function of t
2.what do you understand by ordinary paint of the equation
a0(x)d2y/dx2+a1(x)dy/dx+a2(x)y=0? hence using taylor series expansion find a series solution in powers of x for the equation(2x3-3)d2y/dx2-2xdy/dx+y=0 y(0)=-1
y1(0)=5
1)
Given the system let us express "y" as a function of "t ."
"i)" "3\\dfrac{dx}{dt}+2\\dfrac{dy}{dt}-x+y=t-1"
"ii)\\dfrac{dx}{dt}+\\dfrac{dy}{dt}-x=t+2"
Multiplying equation by "\\times 3" , we get -
And the adding "i)\\ and \\ ii)\\ ," we get -
"=\\dfrac{-dy}{dt}+2x+y=-2t-7"
It gives values of "x" as -
"x=\\dfrac{1}{2}\\dfrac{dy}{dt}-\\dfrac{1}{2}y-t-\\dfrac{7}{2}"
Now , differentiating with respect to t , we get -
"=\\dfrac{dx}{dt}=" "\\dfrac{1}{2}\\dfrac{d^{2}y}{dt^{2}}-\\dfrac{1}{2}\\dfrac{dy}{dt}-1" .
We get the equation as -
"=\\dfrac{1}{2}\\dfrac{d^{2}y}{dt^{2}}-\\dfrac{1}{2}\\dfrac{dy}{dt}-1+\\dfrac{dy}{dt}-(\\dfrac{1}{2}\\dfrac{dy}{dt}-\\dfrac{1}{2}y-t-\\dfrac{7}{2})=t+2"
Which is equivalent to -
"=\\dfrac{1}{2}\\dfrac{d^{2}y}{dt^{2}}+\\dfrac{1}{2}y=\\dfrac{-1}{2}"
And hence the equation becomes -
"=\\dfrac{d^{2}y}{dt^{2}}+y=-1"
Auxiliary equation becomes -
"=m^{2}+1=0"
It's root's becomes as -
"m=+i,-i" ,
It's follows that solution is of form -
"=y(t)=C_1cost+C_2sint +y_p," where "y_p=a"
It's follows that -
"\\dfrac{d^{2}y_p}{dt^{2}}=0" , hence "a=-1." Therefore the solution is the following -
"y(t)=C_1cost +C_2sint-1"
"2)"
Ordinary point of equation is defined as -
A point a is called ordinary point of differential equation when function "p_{1}(x)\\ and \\ p_0(x)" are analytical at "x=a" ,
"=a_0(x)\\dfrac{d^{2}y}{dx^{2}}+a_1(x)\\dfrac{dy}{dx}+a_2(x)y=0"
For , the above equation the ordinary point is called as -
A point "x=x_0" is called ordinary point of differential equation if "a_0(x)\\neq0" at "x=x_0" . The point "x=x_0" is called that ordinary point .
"=(2x^{3}-3)\\dfrac{d^{2}y}{dx^{2}}-2x\\dfrac{dy}{dx}+y=0" "y(0)=-1"
"y^{'}(1)=5"
"Now" , we know that taylor's series expansion is expressed as -
"y(x)=" "y(0)+y^{'}(0)(x-0)+\\dfrac{1}{2!}y^{''}(0)(x-0)^{2}+...."
"=y^{''}(x)=\\dfrac{2xy^{'}(x)}{2x^{3}-3}-\\dfrac{y}{2x^{3}-3}"
Now putting , "x=0," we get -
"y^{''}(0)=0-\\dfrac{y(0)}{-3}"
"y^{''}(0)=\\dfrac{-1}{3}"
"y(x)=-1+5x+\\dfrac{1}{2!}\\dfrac{-1}{3}x^{2}+........."
This is taylor's series of given equation .
Comments
Leave a comment